Предмет: Алгебра,
автор: Аноним
Пожалуйста помогите срочно как сможете
1) 2^x+2 - 2^x+1 + 2^x-1 - 2^x-2<=9
2) 3^2x-1 + 3^2x-2 - 3^2x-4<= 315
3) 2^x - 2^x-4>15
1) 25^x < 6*5^x - 5
2) 3^2x - 3*2^x + 2>0
3) 4^x + 2^x+3 > 20
4) 2^2x - 3*2^x + 2> 0
Ответы
Автор ответа:
0
1)2^х+2 - 2^х+1 + 2^х-1 - 2^х-2<=9
2^х*2^2 - 2^х*2 + 2^х/2 - 2^х/2^2<=9
2^х(4-2+1/2-1/4)<=9
2^х * 2 1/4<=9
2^х<=4
2^х<=2^2
х<=2
2^х*2^2 - 2^х*2 + 2^х/2 - 2^х/2^2<=9
2^х(4-2+1/2-1/4)<=9
2^х * 2 1/4<=9
2^х<=4
2^х<=2^2
х<=2
Автор ответа:
0
1)
x≤2
2)
2x≤6
x≤3
3)
x>4
1)
t² - 6t + 5 < 0
t₁ = 1
t₂ = 5
t∈ (1;5), т.е.
1<t<5
x∈ (0;1)
3)
t² + 8t - 20 >0
D₁ = 16 + 20 = 36
t₁ = -4+6 = 2
t₂ = -4-6 = -10
t∈ (-беск.;-10)U(2;+беск.), но так как t>0, то
t∈ (2; + беск.) или t>2
x>1
4)
t² - 3t + 2 >0
t₁ = 1
t₂ = 2
t ∈ (-беск.; 1)U(2;+беск.)
так как t>0, то
t ∈ (0;1) U (2; + беск.) или:
x ∈ (-беск.;0) U (1;+беск.)
x≤2
2)
2x≤6
x≤3
3)
x>4
1)
t² - 6t + 5 < 0
t₁ = 1
t₂ = 5
t∈ (1;5), т.е.
1<t<5
x∈ (0;1)
3)
t² + 8t - 20 >0
D₁ = 16 + 20 = 36
t₁ = -4+6 = 2
t₂ = -4-6 = -10
t∈ (-беск.;-10)U(2;+беск.), но так как t>0, то
t∈ (2; + беск.) или t>2
x>1
4)
t² - 3t + 2 >0
t₁ = 1
t₂ = 2
t ∈ (-беск.; 1)U(2;+беск.)
так как t>0, то
t ∈ (0;1) U (2; + беск.) или:
x ∈ (-беск.;0) U (1;+беск.)
Похожие вопросы
Предмет: Математика,
автор: mollidast78
Предмет: История,
автор: klaksya777
Предмет: Обществознание,
автор: Olesyalove1808
Предмет: История,
автор: Grigoriy2013